Detection of Uropathogens in Urinary Tract Infection and Their Sensitivity to Many Antimicrobial Agents - Ali, Mohamed R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Urinary tract infections (UTI) are some of the most common infections experienced by humans, exceeded in frequency among ambulatory patient only by respiratory and gastrointestinal infections. It is also the most common cause of nosocomial infection in adults.   A total of three hundred urine sample were collected in age (1-69 years old)   in both gender, with (UTI) symptoms referred to AL-Yarmok Teaching Hospital at Baghdad city during the period from January 2010 till August 2010.  The commonest isolates were Escherichia coli (E.Coli), Proteus mirabilis and Klebsiella pneumoniae (These represented 49.2%, 22 %, and16 % of isolates respectively). The percentage of bacteria incidence in females was higher than male in most of examined samples, except in Klebsiella; it was higher in males .The most positive case was in elder patients than in children. The infection incidences expressed higher level in summer. It reached to peak from August with percentage of   (32 %) and July (24.4 %). The antibiotic sensitivityforstreptomycin,lincomycin,Rifampicin,Chloramphenicol,   Tetracyclin,Ampicillin, Penicillin , Co-trimoxazole, Amoxicillin, Nalidixic acid and Gentamycin was examined , detected species of bacteria were more sensitive to Chloramphenicol(75.6 ) and streptomycin (81.4 ), while the resistances to Tetracycline (100% and Penicillin(100%) were appeared to Escherichia coli